First East Asian record of the genus Alpagut (Hemiptera: Heteroptera: Dipsocoridae), with description of a new species and a note on the metacoxal adhesive pad of Dipsocoridae - Yamada, Kazutaka; Hayashi, Masami (Zootaxa, 2020)
The genus Alpagut Kıyak, 1995, is recorded from East Asia for the first time based on the description of A. masakazui sp. nov. from Japan. Habitus images and illustrations of diagnostic features, including genitalia structures, are provided. The loculus capsulae of A. masakazui sp. nov. is discussed. The presence of a metacoxal adhesive pad is reconfirmed in Dipsocoridae along with a discussion of its morphology.